Immune microenvironment in papillary thyroid carcinoma: roles of immune cells and checkpoints in disease progression and therapeutic implications - Zheng, Xun; Sun, Ruonan; Wei, Tao (Frontiers in Immunology, 2024)
Papillary thyroid cancer (PTC) is the most common type of primary thyroid cancer.Despite the low malignancy and relatively good prognosis, some PTC cases are highly aggressive and even develop refractory cancer in the thyroid. Growing evidence suggested that microenvironment in tumor affected PTC biological behavior due to different immune states. Different interconnected components in the immune system influence and participate in tumor invasion, and are closely related to PTC metastasis. Immune cells and molecules are widely distributed in PTC tissues. Their quantity and proportion vary with the host's immune status, which suggests that immunotherapy may be a very promising therapeutic modality for PTC. In this paper, we review the role of immune cells and immune checkpoints in PTC immune microenvironment based on the characteristics of the PTC tumor microenvironment.Thyroid cancer (TC) represents a prevalent malignancy within the endocrine system, demonstrating a higher incidence in women compared to men and predominantly affecting individuals aged 40 to 50(1, 2). The biological properties of various thyroid cancer subtypes span a broad spectrum. Based on their histological characteristics and cellular origins, thyroid cancers are classified into papillary, medullary, and follicular